(untitled) (Journal of Engineering, 2016)
Fatigue cracking is the most common distress in road pavement. It is mainly due to the increase in the number of load repetition of vehicles, particularly those with high axle loads, and to the environmental conditions. In this study, four-point bending beam fatigue testing has been used for control and modified mixture under various micro strain levels of (250 μƐ, 400 μƐ, and 750 μƐ) and 5HZ. The main objective of the study is to provide a comparative evaluation of pavement resistance to the phenomenon of fatigue cracking between modified asphalt concrete and conventional asphalt concrete mixes (under the influence of three percentage of Silica fumes 1%, 2%, 3% by the weight of asphalt content), and (changing in the percentage of asphalt content) by (0.5% ±) from the optimum. The results show that when Silica fumes content was 1%, the fatigue life increases by 17%, and it increases by 46% when Silica fumes content increases to 2%, and that fatigue life increases to 34 % when Silica fumes content increases to 3% as compared with control mixture at (250 μƐ, 20°C and optimum asphalt content). From the results above, we can conclude the optimum Silica fumes content was 2%. When the asphalt content was 4.4%, the fatigue life has increased with the use of silica fumes by (50%), when asphalt content was 5.4%, the additives had led to increasing the fatigue life by (69%), as compared with the conventional asphalt concrete pavement.